Rancang Bangun Sistem Pemantau Penerima Sinyal Automatic Dependent Surveillance-Broadcast (ADS-B) Berbasis Raspberry Pi dan Antena Ground Plane Sebagai Antena Penerima - Maharani, Fistania Ade Putri; Soim, Sopian; Fadhli, Mohammad (Program Studi Teknik Elektro Universitas Khairun, 2022)
Currently, the technology used for aircraft monitoring is Radar technology. Radar's accuracy is hampered, however, by the fact that while an aircraft is airborne or in flight, it is frequently obscured by clouds, making it difficult to detect the aircraft. Due to constraints in radar technology, Automatic Dependent Surveillance-Broadcast technology was developed to improve the performance of air navigation security. Raspberry Pi, RTL-SDR, and LNA were used as the research method in designing the ADS-B signal receiver monitoring system. The 1090 MHz Ground Plane Antenna is preferable because it has a higher gain and a radiation pattern influenced by radial elements, allowing it to collect a considerably broader signal when combined with Raspberry Pi RTL-SDR and LNA. The monitoring results based on the test data are impressive, generating six aircraft simultaneously, indicating that dump 1090 is very effective at translating the aircraft's ADS-B signal data emitted every 0.5 seconds. ICAO, Altitude and Longitude information are clear Based on tests, the aircraft's ADS-B signal was identified between 4,000 and 38,000 feet over the maximum value, causing the signal to disappear and fail to decode the information. The maximum distance measured during the test was 49.7 kilometers from the elevated location where the ADS-B signal monitoring device was installed. The results of the first test were placed 10 meters above the ground. The result is significantly better than the short antenna position. This significantly improves the accuracy of the ADS-B signal monitoring system and the synchronization of information exchange through real-time monitoring.